Bulky Bartholin's gland cyst: Case report of an incidental finding - Begoña Díaz de la Noval; Irene García Fernández; Beatriz Álvarez Fernández (Elsevier, 2019)
Introduction: Distal blockage of the Bartholin's gland duct can result in the retention of secretions, with consequent formation of a cyst or abscess. Case Report: A 57-year-old woman, in whom a bulky vulvar mass in the left labia majora was detected during cystoscopy for urinary symptoms, was referred to the gynaecology clinic. We performed complete removal of the mass as well as ipsilateral vulvar reconstruction. Histological analysis confirmed a large benign Bartholin's duct cyst without acute infection. Discussion: Epidermoid cysts take a long time to develop and so large cysts are rare. The differential diagnosis of a Bartholin's cystic mass should be considered among many other pathologies in the vulvovaginal area. Treatment with complete surgical excision should be carefully performed, under prophylactic antibiotic coverage if required. Conclusion: Urogynaecological complaints require a careful consideration of the symptoms and an adequate physical examination before additional tests are requested. Although a differential diagnosis can be made preoperatively, confirmation is necessarily histological.